KOMPENSASI DAN KEPUASAN KERJA SEBAGAI ALTERNATIF PENINGKATAN KINERJA KARYAWAN - NAILIN NIKMATUL MAULIDIYAH; Tri Nadhirotur Rofish; Nuruddin Armanto (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2021)
This study aims to determine the effect of compensation on employee performance and the effect of job satisfaction on employee performance. This research is a qualitative research which is sourced from existing theories and relevant empirical research journals. The results of this study showed that compensation has a positive effect on employee performance and job satisfaction has a positive effect on employee performance.